Effect of anti-inflammators on seizures induced by pentylenetetrazole in the Kindling model: a review (Research, Society and Development, 2021)
Introduction: Studies with steroidal and non-steroidal anti-inflammatory drugs in animal models have been carried out in order to verify new therapeutic approaches for the treatment of epilepsy to improve the quality of life of patients with this disease that affects about 65 million people worldwide. Objective: to analyze the relevance of these medications in the treatment of seizures. Methodology: this study is a literature review in order to assess the effects of anti-inflammatory drugs in seizures. Results: the results obtained demonstrate that the animals treated with the steroidal and non-steroidal anti-inflammatory drugs studied had a much lower intensity reduction in convulsive crises without progressing to the Racine 4 scale. Conclusion: It is concluded that the studied steroidal and non-steroidal anti-inflammatory drugs have a protective and reductive effect on inflammatory crises induced by pentilenotetrazol, decreasing the inflammatory cytokines in the central nervous system.